Optogenetics: Emerging strategies for neuropathic pain treatment - Li, Siyu; Feng, Xiaoli; Bian, Hui (Frontiers in Neurology, 2022)
Neuropathic pain (NP) is a chronic condition representing a significant burden for patients, society, and healthcare systems. The treatments for NP are limited, and hardly has desirable efficacy. NP differs from other types of pain, such as nociceptive pain, and the treatments of NP are complex and it is challenging for clinic. This is a comprehensive review of the neuromechanisms and treatments of NP. The neuromechanistic view includes ion channels, neuronal activity, mitochondrial factors, and immune cells in several aspects. This paper reviews the pharmacological, non-pharmacological treatments of NP, and some potential therapeutic directions.